2015
DOI: 10.1016/j.ejpb.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of transmission NIR as a PAT tool for monitoring drug transformation during HME processing

Abstract: The aim of the work reported herein was to implement process analytical technology (PAT) tools during hot melt extrusion (HME) in order to obtain a better understanding of the relationship between HME processing parameters and the extruded formulations. For the first time two in-line NIR probes (transmission and reflectance) have been coupled with HME to monitor the extrusion of the water insoluble drug indomethacin (IND) in the presence of Soluplus (SOL) or Kollidon VA64 hydrophilic polymers. In-line extrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Raman mapping (Lee et al, 2011;Islam et al, 2015)was performed using a Jobin/YvonLabRam 320 instrument equipped with an Olympus microscope (Horiba, Japan)…”
Section: Raman Mapping To Study the Drug Distributionmentioning
confidence: 99%
“…Raman mapping (Lee et al, 2011;Islam et al, 2015)was performed using a Jobin/YvonLabRam 320 instrument equipped with an Olympus microscope (Horiba, Japan)…”
Section: Raman Mapping To Study the Drug Distributionmentioning
confidence: 99%
“…[44]. [DE26]Process parameter chart during a scale-up via hot melt-extrusion (HME) [72]. Using the batch monitoring data and process information to predict the quality of the product PAT Level V Feedback control of the process to maintain the quality of the product…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that, with the increase in screw speed from 50 rpm to 400 rpm (temperature constant) during a scale-up, the torque increased from 8.8 Nm to 12.7 Nm, impacting the resultant SMEC values, which exhibited a significant effect on the state of the extrudates [72]. Similarly, the increasing screw speed favored intense mixing inside the barrel by increasing the pressure (8 bars) and the torque (12.7 Nm).…”
Section: Scale-up Models and Formulas In Hmementioning
confidence: 99%
“…The existence of the single phase homogenous system in all formulations indicates that the drug molecule has been encapsulated within the polymeric matrices. This could also happen due to the molecular interaction as a result of single-phase distribution [30].…”
Section: Raman Mappingmentioning
confidence: 99%